2005
DOI: 10.1111/j.1600-0463.2005.apm_183.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerococcus urinae: polyphasic characterization of the species

Abstract: A polyphasic characterization of Aerococcus urinae is presented. In this study the intraspecies relationships between 26 strains of varying geographical origin were examined by phenotypic tests, ribotyping and multilocus enzyme electrophoresis. The results demonstrated two main phenotypic patterns that could be distinguished in tests for hydrolysis of aesculin, and acid production from amygdalin and salicin. Strains were either negative (n=19) or positive (n=6) in these tests. One strain had a deviating patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…While MicroSeq potentially has higherquality sequence data because it relies on type strains, we have demonstrated that use of a single type strain to represent entire taxa is often inadequate. The sequence heterogeneity of specific microorganisms within SmartGene is particularly valuable for identifying species, since many studies have demonstrated the existence of distinct interspecies and intraspecies variability (4,8,10,12,26). The software also allows selection of ambiguous base codes as a feature for BLAST searches which can be particularly useful for those microorganisms with high numbers of ambiguous bases (e.g., Nocardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…While MicroSeq potentially has higherquality sequence data because it relies on type strains, we have demonstrated that use of a single type strain to represent entire taxa is often inadequate. The sequence heterogeneity of specific microorganisms within SmartGene is particularly valuable for identifying species, since many studies have demonstrated the existence of distinct interspecies and intraspecies variability (4,8,10,12,26). The software also allows selection of ambiguous base codes as a feature for BLAST searches which can be particularly useful for those microorganisms with high numbers of ambiguous bases (e.g., Nocardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Both species were isolated from blood of patients suffering from urogenic sepsis, in few cases from patients with complicating IE and casuistically isolated from other foci [9]. Recognition of both species may be limited by their fastidious growth, often requiring supplementation with CO 2 for optimal growth [6,10]. Aerococci share colony morphology with α-hemolytic streptococci and have a microscopic appearance similar to staphylococci, which adds to the risk of misinterpretation and misidentification [9].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Isolates from both species are characterized by Staphylococcus -like morphology in Gram stains with growth characteristics resembling α-hemolytic streptococci on blood containing agar plates, a negative catalase reaction, a consistent antibiogram demonstrating susceptibility to β-lactams, and for A . urinae resistance to sulfonamides and aminoglycosides [ 5 ]. Recognition of the species may be harmed by their fastidious growth, which not seldom require supplementation with CO 2 for optimal growth [ 5 ].…”
Section: Introductionmentioning
confidence: 99%